Analisis Pengembangan Kurikulum Pendidikan Agama Islam di SQ-Darul Fattah Bandar Lampung: Analisis Pengembangan Kurikulum Pendidikan Agama Islam di SQ-Darul Fattah Bandar Lampung - Akhmad khoiri; Dendi Wahyudi (ISLAM EDU : Jurnal Ilmiah Pendidikan Agama Islam, 2023)
The curriculum is often ignored in the educational process, even though without the curriculum, education cannot deliver the educational process to the desired destination. Darul Fattah Quran School Bandar Lampung is one of the favorite private schools in Bandar Lampung, which has its own way of developing Islamic religious education curriculum to create a generation with noble character, tahfizd and intelligence. The purpose of this study is to explore and analyze how the development of Islamic religious education curriculum in SQ-DF Bandar Lampung. While the method in this study uses literature research, namely qualitative and descriptive research. The goal is to describe the state or phenomenon as it is by obtaining data sources from various documents that support this research. The results of the analysis in this study are: 1). SQ-Darul Fattah has clear PAI curriculum development objectives. 2). SQ-Darul Fattah applies good learning methods in developing the PAI curriculum. 3). SQ-Darul Fattah applies strategy in growing PAI learning miat for students. 4). SQ-Darul Fattah facilitates learning media needed in PAI curriculum development. 5). SQ-Darul Fattah does not put the burden of tasks on students at home because SQ-DF implements complete learning at school. 6). SQ-Darul Fattah implements PAI activities outside the classroom that can support Islamic religious education in the classroom. This out-of-class PAI activity is a flagship educational program in the development of the PAI curriculum at SQ-DF Bandar Lampung.